(untitled) (SCHOOLAR: Social and Literature Study in Education, 2023)
Exaggeration in religion is a dangerous disease. Exaggeration is forbidden and forbidden according to the Shari’ah. This attitude can bring bad consequences for each individual and society. Based on the above background, this study aims to identify and describe religious moderation at the Islamic Boarding School Darun Najah Karangploso Malang from the perspective of Kyai and Ustadz. This research uses a qualitative descriptive research type. Research data were collected using observation, interview and documentation methods. In this study the researchers used inductive data analysis, namely analyzing data based on specific facts to produce conclusions about the facts of the events that occurred. Teachers do not only rely on learning strategies, Kyai and Teachers also use the latest social media. Equipped with understandings of religious moderation by Islamic boarding schools’ Kyai and teachers, they can make students at the Darun Najah Islamic Boarding School have good social ethics with the community, make wise decisions, and be tolerant of anyone in accordance with the values of religious moderation.